23+11+2c=10-2c

Simple and best practice solution for 23+11+2c=10-2c equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 23+11+2c=10-2c equation:


Simplifying
23 + 11 + 2c = 10 + -2c

Combine like terms: 23 + 11 = 34
34 + 2c = 10 + -2c

Solving
34 + 2c = 10 + -2c

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '2c' to each side of the equation.
34 + 2c + 2c = 10 + -2c + 2c

Combine like terms: 2c + 2c = 4c
34 + 4c = 10 + -2c + 2c

Combine like terms: -2c + 2c = 0
34 + 4c = 10 + 0
34 + 4c = 10

Add '-34' to each side of the equation.
34 + -34 + 4c = 10 + -34

Combine like terms: 34 + -34 = 0
0 + 4c = 10 + -34
4c = 10 + -34

Combine like terms: 10 + -34 = -24
4c = -24

Divide each side by '4'.
c = -6

Simplifying
c = -6

See similar equations:

| 20x+5x=15 | | 1200+40x=3000 | | -2-7b=12 | | 18t^2+18-32t^3=0 | | 2(2x+3)+-2=5 | | -2b-7=12 | | 3(8m-13)+10=17(3+2m) | | 10+2m=16 | | 2(2x+3)-2=2 | | (x*x)-3x=0 | | -2-7=12 | | 1/5x+1/2=3/10x-1 | | a=bx+6x+d | | 4(-2+x)=5(x+.5) | | -3x+6-5=5x+4 | | 8c-9=47 | | 34x+5=175 | | 0=2x^2+11x-9 | | 19x^6-4x^4+11x^3= | | 0=.5x^2+x-2 | | 3x+36=6(x+3) | | -6+13=7x | | 2v^4+3v^3-27v^2= | | 0.1x+2.6x=8-1.8+2.5x | | -3x-2(x+6)+7=7x-9 | | 2(2x+5)-(4x-9)=3(3-4x) | | 12-7b=-2 | | -9x+1=-71 | | -3z=-10 | | 7-5(8-3p)=-123 | | 36r^3-r=0 | | -25=-5+5y |

Equations solver categories